Stage-specific efficacy of pharmacological interventions on gait impairments in Parkinson’s disease - Zhang, Jun; Chen, Le; Li, Jun (Frontiers in Neurology, 2025)
ObjectiveThis study aims to clarify the variations and the therapeutic effects of medicine on gait by analyzing the gait characteristics before and after medication in various stages of Parkinson’s disease (PD).MethodsThis prospective study included 60 patients with PD [Hoehn-Yahr (H-Y) stage 1–4] at the department of Neurology of Beijing Tsinghua Changgung Hospital, and 30 gender and age - matched healthy controls. The ReadyGo system was used to record gait parameters. The levodopa challenge test was applied to assess the therapeutic effect of medicine on gait.ResultsWe observed a shorter stride length and stride height, a longer stride time and turn-around time, and a reduction of stride speed in the PD group compared with the healthy control group significantly. No significant changes were noted in the variability of stride parameters (stride frequency variability and stride length variability). The radar chart demonstrated a gradual decline in gait parameters as the disease progressed. Compared to healthy control group, significant differences in stride speed and stride time were observed from H-Y stage 1 (p < 0.05) while stride length, stride width, and turn-around time were from H-Y stage 2 (p < 0.05), and step height is H-Y stage 3 (p < 0.05). After administering levodopa, there was a marked improvement in stride speed (p = 0.009) and turn-around time (p = 0.005). The most notable improvements in stride speed and turn-around time occurred at H-Y stage 3. Improvements in non-gait domains were more notable across all stages of PD patients than gait domains.ConclusionGait changes can serve as a new early diagnosis marker for PD because of the early significant change in gait parameters especially on stride speed and stride time. As the disease advances, various gait parameters gradually deteriorate, suggesting that objective gait monitoring can provide a reference method to dynamically observe PD progression. Unlike the previous view that medicine has limited effect on gait, this study found that although the effect of medicine on gait is not as remarkable as that on tremor and rigidity, medicine can still effectively improve gait, especially in the patients with advanced PD.